2014
DOI: 10.3130/jaabe.13.475
|View full text |Cite
|
Sign up to set email alerts
|

Economic Analysis of Korea Green Building Certification System in the Capital Area Using House-Values Index

Abstract: Since 1980, there have been widespread efforts by international organizations, governments, and research centers to achieve sustainable development. In Korea, green building certification has been developed and adopted for various types of buildings. However, although research has been conducted regarding the economic benefits of the Korean green building certification system, no research efforts have compared the average house-values between green building certified and non-certified buildings. In addition, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The study concluded that the property value of a G-SEED certified building was higher than a non-certified building. Furthermore, the study suggested that the proximity of transportation is one of main factors to positively affect property's value [14]. In addition, Kim, Son, and Son (2020) reported that the economic value of LEED certified educational building was higher than non-certified building.…”
Section: Factors Affecting Apartment Pricingmentioning
confidence: 99%
“…The study concluded that the property value of a G-SEED certified building was higher than a non-certified building. Furthermore, the study suggested that the proximity of transportation is one of main factors to positively affect property's value [14]. In addition, Kim, Son, and Son (2020) reported that the economic value of LEED certified educational building was higher than non-certified building.…”
Section: Factors Affecting Apartment Pricingmentioning
confidence: 99%
“…To effectively control this factor, the studied data were limited to parcels for "unimproved" lands only. The real property values consist of land plus any improvements attached to the land (Son et al 2013). Externalities like the economic condition may affect the value of improved lands.…”
Section: Sustainable Land Developmentmentioning
confidence: 99%
“…Lee and Yeom 11), 12) and Kwon et al 10) conducted satisfaction surveys on the residents of certified and general apartments, and showed improvement directions focused on criteria that demonstrated low satisfaction. Also, Son et al 17) investigated and showed the economic benefits of the Korean green building certification system.…”
Section: Introductionmentioning
confidence: 99%